Glory of fire retardants in Li-ion batteries: could they be intrinsically safer? - Mishra, Rajat; Anne, Mounika; Das, Sayan; Chavva, Tarunikaa; Shelke, Manjusha V.; Pol, Vilas G. (Advanced Sustainable Systems, 2024)
Lithium-ion batteries (LIBs) have dramatically transformed modern energy storage, powering a wide range of devices from portable electronics to electric vehicles, yet the use of flammable liquid electrolytes raises thermal safety concerns. Researchers have investigated several ways to enhance LIB's fire resistance. Fire retarding molecules functions through cooling effects, scavenging radicals, and forming protective barriers. Incorporating fire-suppressing molecules within the LIBs aims to delay or mitigate thermal runaway scenarios, reducing the risks of fires or explosions. Achieving an optimal balance between safety and performance is a major obstacle in the design of intrinsically safer LIBs. Therefore, it is important to consider their effects on LIB's performance, long-term stability, and environmental impact. To overcome these challenges, collaborative research efforts among academia, industry, and regulatory sectors are necessary. This article reviews state-of-the-art literature associated with LIBs safety or even fire mitigation by introducing solid-state or quasi-solid-state electrolytes as well as modified liquid electrolytes. Moreover, the effectiveness of various strategies in making LIBs intrinsically safer is critically evaluated with an emphasis on fire retardants followed by shedding some light on the remaining challenges.